1993
DOI: 10.1093/clinchem/39.4.667
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory chain enzyme activities in lymphocytes from untreated patients with Parkinson disease

Abstract: Respiratory chain enzyme activities were studied in lymphocytes from patients with Parkinson disease (PD) (n = 16) and age-matched control subjects (n = 15). The patients had received no therapy before the study was conducted. Complex I, III, and IV activities were significantly lower (P < 0.05) in patients than in control subjects. A complex I defect was found in one patient, whereas complex IV was defective in another. Two patients had combined defects of both complexes. The use of lymphocytes for inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 0 publications
2
29
1
Order By: Relevance
“…This biochemical defect is the same as that produced in animal models of parkinsonism by MPTP and adds further support to the proposition that PD may be due to an environmental toxin with action(s) similar to those of MPTP.'' Further studies confirmed mitochondrial abnormalities in the periphery using platelet-rich preparations from another cohort of patients (Krige et al, 1992;Schapira et al, 1992) or blood lymphocytes (Barroso et al, 1993). Authors concluded that: ''our study supports the hypothesis that a biochemical defect in the respiratory chain may be involved in the pathogenesis of PD.''…”
Section: Influence Of Pesticides and Related Environmental Toxics In supporting
confidence: 78%
“…This biochemical defect is the same as that produced in animal models of parkinsonism by MPTP and adds further support to the proposition that PD may be due to an environmental toxin with action(s) similar to those of MPTP.'' Further studies confirmed mitochondrial abnormalities in the periphery using platelet-rich preparations from another cohort of patients (Krige et al, 1992;Schapira et al, 1992) or blood lymphocytes (Barroso et al, 1993). Authors concluded that: ''our study supports the hypothesis that a biochemical defect in the respiratory chain may be involved in the pathogenesis of PD.''…”
Section: Influence Of Pesticides and Related Environmental Toxics In supporting
confidence: 78%
“…Such a scenario would align with the findings of this study. In support of this, numerous studies on mitochondrial respiration in various cell types in small cohorts of ante-mortem PD patients have failed to produce conclusive findings (Ambrosi et al, 2014;Barroso et al, 1993;Bravi et al, 1992;Cronin-Furman et al, 2013;Esteves et al, 2010;Martin et al, 1996;Parker and Swerdlow, 1998;Shinde and Pasupathy, 2006;Yoshino et al, 1992). Importantly, recently, a larger study examining mitochondrial respiration in immortalized lymphocytes from 30 patients found enhanced respiratory activity with no functional deficit (Annesley et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…D1 and D2) and N-methyltransferase related to PD pathogenesis in lymphocytes from PD patients (Barbanti et al, 1999). In addition, impaired respiratory chain enzyme activities were detected in lymphocytes of PD patients, suggesting mitochondrial dysfunction in these cells (Barroso et al, 1993;Maruyama et al, 2000). Increased risk of apoptosis was also reported (Blandini et al, 2004;Calopa et al, 2010;Del Rio et al, 2004).…”
Section: The Activation Of Lymphocytes In Pdmentioning
confidence: 94%